Flow: una pausa para fluir en el trabajo (2020)
This project explores the impact of music on emotions and mood. It was developed in a specific context, in which the challenge of maintaining a stable and positive mental state is clear: the work environment. Thus, a tool is created that, through the psychology of music and the concept of active pause, promotes and helps the well-being of people while they are at work. For this, the whole concept of the brand and the service experience is developed, which is intended to impact small and medium-sized companies.